Analisis Struktur Modal terhadap Kinerja Keuangan Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 : Studi Kasus PT Blue Bird Tbk - Sri Febrianti (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
"Capital Structure Analysis of the Financial Performance of Companies Listed on the Indonesian Stock Exchange for the 2018-2022 Period (Case Study of Pt Blue Bird Tbk)". under the guidance of Mrs. Dr. Milka Pasulu, SE., M.Si, and Fausiah, S.E., M.Si. This research aims to determine the effect of capital structure policy on the financial performance of PT Blue Bird Tbk. The research sample is the 31 December financial report regularly for 5 years in accordance with the research period required for the periods 2018, 2019, 2020, 2021 and 2022 (The financial report as of 31 December is a financial report that has been audited). The results of the analysis found that the company PT Blue Bird Tbk for the 2018 – 2022 period, where analysis of capital structure policies to measure financial performance obtained poor results. Regarding this, the values ​​obtained from DER, DAR, ROA and ROE measurements experience fluctuating percentages (rising and falling).